The genome sequence of the Large Red Tailed Bumble Bee, Bombus lapidarius (Linnaeus, 1758) [version 1; peer review: 2 approved] - Matthew N. Smith; Olga Sivell; Duncan Sivell (Wellcome Open Research)
We present a genome assembly from an individual female specimen of Bombus lapidarius (Large Red Tailed Bumble Bee; Arthropoda; Insecta; Hymenoptera; Apidae). The genome sequence has a total length of 368.50 megabases. Most of the assembly (81.04%) is scaffolded into 18 chromosomal pseudomolecules. The mitochondrial genome has also been assembled and is 28.11 kilobases in length.